COVID-19 in Children with Congenital Heart Diseases: A Multicenter Case Series from Iran. (19th April 2021) - Esmaeeli, Hassan; Ghaderian, Mehdi; Zanjani, Keyhan Sayadpour; Ghalibafan, Seyyedeh Fatemeh; Mahdizadeh, Mehrzad; Aelami, Mohammad Hassan
Abstract : Background . Promptly discovering and counteracting COVID-19 is critical as it could have catastrophic effects. As an asymptomatic group, children are highly susceptible to be misdiagnosed, especially those suffering from underlying diseases. Furthermore, discriminating the direct effects of the virus from those of the underlying diseases can pose a dilemma to physicians. This case series aims to determine the relationship between COVID-19 and various types of congenial heart disease among children. Patients and Methods . Seven patients from three different medical centers were enrolled. Their detailed demographic information, past medical history, symptoms, type of congenital heart diseases, imaging tests, laboratory tests, medications, and outcomes were analyzed. Results . The patients included 4 infants, 1 child, and 2 adolescents, with a median age of 9 months and a majority of boys. All of them had either obstructive lesions (right or left ventricular outflow tracts) or significant pulmonary hypertension. The more common clinical symptoms were cough, dyspnea, and fever. Two patients did not survive the illness. Conclusion . Prompt treatment of patients with a combination of COVID-19 and severe obstructive cardiac pathology or pulmonary hypertension is essential due to a risk for serious and/or fatal consequences.